Stabilization of uncertain switched discrete-time systems against actuator faults and input saturation. (February 2020) - Sakthivel, R.; Susana Ramya, L.; Ma, Yong-Ki; Malik, Muslim; Leelamani, A.
Abstract: This paper studies the robust fault-tolerant stabilization problem for a class of uncertain switched discrete-time systems subject to time delays, actuator faults and input saturation by using delta operator approach. By constructing an appropriate Lyapunov–Krasovskii functionals in delta domain, a new set of sufficient conditions is provided for the stability of the delta operator time delay switched systems. More precisely, gain matrices of the fault-tolerant controller can be computed by solving the linear matrix inequalities and the proposed controller can robustly stabilize the uncertain delta operator time delay switched system for all admissible parameter perturbations. Further, in order to obtain a maximal estimate of the domain of attraction, an LMI based optimization algorithm is presented. It is noted that a better control performance can be obtained for small sampling periods by using delta operator approach than using shift operator. Finally, numerical examples with simulation results are presented to illustrate the effectiveness and potential of the developed control design technique.